2021
DOI: 10.21503/lex.v19i28.2318
|View full text |Cite
|
Sign up to set email alerts
|

Contratación electrónica y los delitos informáticos. En protección al consumidor en el Perú

Abstract: El artículo tiene por objeto revisar los antecedentes y retos de la contratación electrónica en el Perú, con especial énfasis en la protección legal de la que disponen los usuarios frente a los delitos informáticos. Para ello, se realizó una búsqueda bibliográfica a fin de tener un mejor entendimiento del tema en cuestión. Luego del análisis realizado, se encontró que en el Perú aún no se ha implementado las normas necesarias que aseguren la confianza y seguridad de los usuarios; empero, ya se está dando los p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
2
0
1
Order By: Relevance
“…The trend analysis of the number of publications analyzed shows a positive trend over the years, as shown in Figure 2: There are fewer Latin American studies (Chile 3, Colombia 1, Mexico 2), which show the need to address "cybercrime" as an issue of social necessity in the region, whose evidence will help to seek methods of prevention and action against vulnerable situations of misuse of technology in criminal acts. The figure (3) shows the number of publications by country of origin, which are part of this research; a predominant contribution of European studies is observed, especially from Spain ( 12) and the United Kingdom (7).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The trend analysis of the number of publications analyzed shows a positive trend over the years, as shown in Figure 2: There are fewer Latin American studies (Chile 3, Colombia 1, Mexico 2), which show the need to address "cybercrime" as an issue of social necessity in the region, whose evidence will help to seek methods of prevention and action against vulnerable situations of misuse of technology in criminal acts. The figure (3) shows the number of publications by country of origin, which are part of this research; a predominant contribution of European studies is observed, especially from Spain ( 12) and the United Kingdom (7).…”
Section: Methodsmentioning
confidence: 99%
“…Cybercrime in a general context is the unlawful conduct affecting computer systems and data, besides other legal assets of criminal relevance committed using information or communication technologies. [7]. Computer crimes are seen from two approaches: for the first one, they are just conventional crimes that take on new life from the use of computer devices and Internet services and applications; for the second one, it is the commission of intangible crimes using technologies, such as the distribution of viruses or malicious programs through the network, attacks on websites, and software piracy.…”
Section: A Cybercrimementioning
confidence: 99%
“…Un ejemplo de este tipo de ciberataque se menciona en (Riega Virú et al, 2021) , donde se dice que en mayo del año 2019, una ciudad en Estados Unidos, recibió un ataque de ransomware que impidió el acceso a miles de empleados y residentes a su computadora, lo que género que no se pudiese pagar facturas o acceder a sus correos electrónicos, el rescate que se pidió en este caso fue de 100 mil euros en bitcoins. Otro caso que también llama la atención es lo sucedido en mayo del 2021, donde el gran Oleoducto Colonial ubicado en Estados Unidos fue cerrado por un ciberataque, y esto puso en peligro cerca del 45% de suministros de combustible de la costa este del país lo que genero un pánico en la población incrementando la demanda por combustible e intensificando el problema de suministro, en este caso se llegó a pagar cerca de 5 millones de dólares en criptomonedas el mismo día, sin embargo esto no impidió que el problema creciese por el pánico que se generó.…”
Section: Introductionunclassified